2019
DOI: 10.4028/www.scientific.net/msf.959.125
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Flotation: State of the Art and its Potential for the Separation of Fine and Ultrafine Mineral Particles

Abstract: Critical raw materials (CRMs) are of primary importance for energy storage systems as needed for electromobility. Many mineral deposits which contain CRMs are low-grade ores. To liberate the CRMs, a grinding of the mineral ores to very fine sizes below 20 µm particle size is necessary. However, the present class of industrial flotation plants fail to extract such fine and ultrafine particles. To improve the recovery in fine particle flotation, techniques have been developed which attempt to agglomerate the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…These processes are selective flocculation, agglomerate flotation, electrocoagulation/flotation, precipitate flotation, oil flotation, shearflocculation/flotation, and carrier flotation, 1,6 among which carrier flotation distinguishes itself from other processes as it has an advantage in reducing the unselective entrainment of gangue particles into the concentrate. 7 Carrier flotation can be considered as a hydrophobic flocculation−flotation process in which fine hydrophobic particles are first preferentially collected by larger hydrophobic carrier particles so that the apparent separation size of valuable particles increases to the extent that allows them to be efficiently recovered by conventional flotation. Chia and Somasundaran examined the stability of aggregates consisting of anatase and calcite particles formed under various flotation chemistry and hydrodynamic conditions using a modified DLVO theory and revealed that the improved performance of carrier flotation was attributed to the enhanced strong aggregation between fine anatase and coarse carrier (i.e., calcite) particles under intense agitation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These processes are selective flocculation, agglomerate flotation, electrocoagulation/flotation, precipitate flotation, oil flotation, shearflocculation/flotation, and carrier flotation, 1,6 among which carrier flotation distinguishes itself from other processes as it has an advantage in reducing the unselective entrainment of gangue particles into the concentrate. 7 Carrier flotation can be considered as a hydrophobic flocculation−flotation process in which fine hydrophobic particles are first preferentially collected by larger hydrophobic carrier particles so that the apparent separation size of valuable particles increases to the extent that allows them to be efficiently recovered by conventional flotation. Chia and Somasundaran examined the stability of aggregates consisting of anatase and calcite particles formed under various flotation chemistry and hydrodynamic conditions using a modified DLVO theory and revealed that the improved performance of carrier flotation was attributed to the enhanced strong aggregation between fine anatase and coarse carrier (i.e., calcite) particles under intense agitation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, a large range of modified flotation processes, in which flotation was performed after increasing the apparent particle size of target fine/ultrafine particles, were developed. These processes are selective flocculation, agglomerate flotation, electrocoagulation/flotation, precipitate flotation, oil flotation, shear-flocculation/flotation, and carrier flotation, , among which carrier flotation distinguishes itself from other processes as it has an advantage in reducing the unselective entrainment of gangue particles into the concentrate …”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned particle size separation method has been widely used in mineral, chemical, environmental, and other industries [4][5][6]. However, the mineral process suffers from both some new tendencies (for instance, the decreasing processed particle size [7,8]) and inherent weaknesses (such as unsatisfactory efficiency and sharpness [9] and fish-hook effect [10]).…”
Section: Introductionmentioning
confidence: 99%
“…Froth flotation is one of the most widely used methods for the separation, enrichment, and purification of metal ores, industrial minerals, and coals . Recently, the use of auxiliary methods involving ultrasound, carriers, and microwaves in mineral flotation has attracted significant attention. Unfortunately, the time and economic demands of these research approaches have hindered their development, and these methods are yet to be practiced widely. In recent years, remarkable growth in the commercial production of valuable minerals from refractory complex ores has promoted the design and development of selective froth flotation reagents, which is the key to the remarkable success in enhancing the flotation separation efficiencies of valuable minerals from these ores. However, the development of new collector materials is potentially expensive.…”
Section: Introductionmentioning
confidence: 99%